System analysis of erosion-bed processes - M. A. Georgieva (Современная наука и инновации)
Erosion-bed processes can be caused by various factors, such as high speed of water flow, uneven flow, change in the direction of water flow, water coming to the surface from aquifers and the groundwater horizon, the presence of variability in the channel and other factors. A mathematical description of the processes under consideration in their complex relationships and system analysis allows us to predict the development of erosion-bed processes, such as: changes in the strength of the channel, an increase in the speed of water flow, the formation of local waterfalls and rapids, dam breaks and other dangers. In addition, the removal of material from the riverbed can lead to pollution of water bodies and disruption of the ecosystem.